Re-conceptualizing Toponyms as the repository of Moken traditional ecological knowledge: A case study of Surin Islands - Kraisame, Sarawut; Thawornpat, Mayuree (Kasetsart Journal of Social Sciences, 2023)
Toponyms or place names are a crucial language component in every language. They usually represent topographic environment or cultural elements of specific groups or areas. Toponyms constitute the linkage between humans and the landscapes surrounding them. Further, toponyms are the repository of traditional ecological knowledge (TEK) of each individual group. Moken people in Surin Islands store various kinds of ecological knowledge in their Moken toponyms. In view of the foregoing, this research aims to disclose the repository of Moken people to illustrate the traditional ecological knowledge (TEK) underpinning the toponyms. This study adopted the TEK framework as proposed by Jones (2016) to reveal the findings. This research is a qualitative study based on 94 toponyms in the Moken language and culture documentation project (Klatalay et al., 2013; Kraisame 2016; 2018). Salient findings indicated that the structure of Moken toponyms consists of a primary element and a core element. Specifically, Moken people use lexicons relating to beach, rock/stone and coral, cape, island, and direction as topographical names in the primary element, whereas those relating to subsistence names, social names, memory names, and religio-spiritual names are used in the core element. Also reported in the study is that these elements correlate with the cultural landscape concept of Sauer (1969). In the light of these findings, it can be argued that toponyms are not simply names denoting places, but they constitute a repository of individual groups that carry the torch of knowledge from one generation to the next.